2010
DOI: 10.5194/bg-7-753-2010
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of carbonyl sulfide (COS) between the atmosphere and various soils in China

Abstract: Abstract. Using a dynamic enclosure, the exchange rates of carbonyl sulfide (COS) between the atmosphere and 18 soils from 12 provinces in China were investigated. The emission or uptake of COS from the soils was highly dependent on the soil type, soil temperature, soil moisture, and atmospheric COS mixing ratio. In general, with the only exception being paddy soils, the soils in this investigation acted as sinks for atmospheric COS under wide ranges of soil temperature and soil moisture. Two intensively inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 56 publications
0
25
1
Order By: Relevance
“…Even at 100 ppt, only five of the soils had positive net COS fluxes indicating that the COS compensation point was lower than 100 ppt for the majority of the soils. This is consistent with previous studies on oxic soils (Kesselmeier et al, 1999;Liu et al, 2010) but contradictory to the results of Lehman and Conrad (1996) who found much higher compensation points. This apparent contradiction might be explained by the fact that Lehman 25 and Conrad explored a much higher and wider range of COS concentrations (60-410 ppb) where different COS consumption processes might take place (e.g.…”
Section: Relative Importance Of Gross Cos Production To the Net Soil contrasting
confidence: 55%
See 2 more Smart Citations
“…Even at 100 ppt, only five of the soils had positive net COS fluxes indicating that the COS compensation point was lower than 100 ppt for the majority of the soils. This is consistent with previous studies on oxic soils (Kesselmeier et al, 1999;Liu et al, 2010) but contradictory to the results of Lehman and Conrad (1996) who found much higher compensation points. This apparent contradiction might be explained by the fact that Lehman 25 and Conrad explored a much higher and wider range of COS concentrations (60-410 ppb) where different COS consumption processes might take place (e.g.…”
Section: Relative Importance Of Gross Cos Production To the Net Soil contrasting
confidence: 55%
“…Although this is the first study to demonstrate a significant relationship between soil N concentration and gross COS 5 production rates, previous studies have observed shifts in the magnitude of net COS and CS2 fluxes upon fertilisation with nitrate in both deciduous and evergreen coniferous forests (Melillo & Steudler, 1989). In addition a number of studies on agricultural soils in the US and China have observed large temperature-sensitive emissions of COS Liu et al, 2010;Maseyk et al, 2014;Whelan & Rhew, 2015). Currently, the mechanisms for the observed link between sulphur and nitrogen cycling in soils is still not understood.…”
Section: Drivers and Mechanisms Of Cos Production Across European Soimentioning
confidence: 98%
See 1 more Smart Citation
“…Several field studies provide support for this by showing that soils generally act as an OCS sink when measured at ambient concentrations (Castro and Galloway, 1991;Kuhn et al, 1999;J. Liu et al, 2010;Steinbacher et al, 2004;White et al, 2010;Yi et al, 2007) and that the uptake rate is reduced when the soil is autoclaved (Bremner and Banwart, 1976).…”
Section: J Ogée Et Al: a New Mechanistic Framework To Predict Ocs Fmentioning
confidence: 97%
“…In some extreme cases where P 25 fully dominates over f CA , our model could even predict OCS fluxes close to zero at temperatures below ∼ 10 • C that would increase exponentially at warmer temperatures, as it has been observed in some agricultural soils (J. Liu et al, 2010;Maseyk et al, 2014;Whelan and Rhew, 2015).…”
Section: Sensitivity To Soil Ca Activity and Ocs Emission Ratesmentioning
confidence: 99%